1993
DOI: 10.4049/jimmunol.151.9.4625
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-beta 1 is required for secretion of IgG of all subclasses by LPS-activated murine B cells in vitro.

Abstract: Addition of transforming growth factor-beta 1 (TGF-beta 1) to in vitro cultures of murine B cells activated with bacterial LPS selectively stimulates IgG2b and IgA class switching and decreases cellular proliferation. To assess a possible role for endogenous TGF-beta in modulating the Ig isotypes produced by LPS-activated cells, we utilized a neutralizing anti-TGF-beta mAb to abrogate endogenous TGF-beta activity. Anti-TGF-beta antibody, over a range of relatively low cell densities, strikingly inhibited both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moreover, it has been proposed that TGF‐β also limits the proliferation of human B cell precursors and ultimately their differentiation resulting in decreased IgM and IgD formation by inhibiting Ig mRNA synthesis and the switch from membrane‐bound form to secreted Ig form in human B cells 23,38 . However, some studies showed low‐dose TGF‐β1 promoted, whereas high‐dose inhibited IgG antibody secretion in murine B cells 21 . Interleukin‐21 (IL‐21) augments IgA production in PPs by promoting direct class switching and differentiation to IgA + B cells via the Jak–STAT pathway 10,12,39 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, it has been proposed that TGF‐β also limits the proliferation of human B cell precursors and ultimately their differentiation resulting in decreased IgM and IgD formation by inhibiting Ig mRNA synthesis and the switch from membrane‐bound form to secreted Ig form in human B cells 23,38 . However, some studies showed low‐dose TGF‐β1 promoted, whereas high‐dose inhibited IgG antibody secretion in murine B cells 21 . Interleukin‐21 (IL‐21) augments IgA production in PPs by promoting direct class switching and differentiation to IgA + B cells via the Jak–STAT pathway 10,12,39 .…”
Section: Discussionmentioning
confidence: 99%
“…20 In LPS-treated murine B cells, a low dose of TGF-β1 was promoted while a high dose inhibited IgA antibody secretion. 21 TGF-β1 and TGF-β3 suppressed B cell proliferation, differentiation of plasma cells and production of IgA in human peripheral blood B cells. 22,23 Accumulating evidence thus indicates that TGF-β1 affects IgA production, and this may differ between species, and it remains unclear how TGF-β1 regulates IgA antibody formation in porcine B cells.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations